Impaired mitochondrial dynamics and removal of the damaged mitochondria in diabetic retinopathy - Kumari Alka; Jay Kumar; Renu A. Kowluru (Frontiers in Endocrinology, 2023)
IntroductionMitochondrial dynamic plays a major role in their quality control, and the damaged mitochondrial components are removed by autophagy. In diabetic retinopathy, mitochondrial fusion enzyme, mitofusin 2 (Mfn2), is downregulated and mitochondrial dynamic is disturbed resulting in depolarized and dysfunctional mitochondria. Our aim was to investigate the mechanism of inhibition of Mfn2, and its role in the removal of the damaged mitochondria, in diabetic retinopathy.MethodsUsing human retinal endothelial cells, effect of high glucose (20mM) on the GTPase activity of Mfn2 and its acetylation were determined. Role of Mfn2 in the removal of the damaged mitochondria was confirmed by regulating its acetylation, or by Mfn2 overexpression, on autophagosomes- autolysosomes formation and the mitophagy flux.ResultsHigh glucose inhibited GTPase activity and increased acetylation of Mfn2. Inhibition of acetylation, or Mfn2 overexpression, attenuated decrease in GTPase activity and mitochondrial fragmentation, and increased the removal of the damaged mitochondria. Similar phenomenon was observed in diabetic mice; overexpression of sirtuin 1 (a deacetylase) ameliorated diabetes-induced inhibition of retinal Mfn2 and facilitated the removal of the damaged mitochondria.ConclusionsAcetylation of Mfn2 has dual roles in mitochondrial homeostasis in diabetic retinopathy, it inhibits GTPase activity of Mfn2 and increases mitochondrial fragmentation, and also impairs removal of the damaged mitochondria. Thus, protecting Mfn2 activity should maintain mitochondrial homeostasis and inhibit the development/progression of diabetic retinopathy.